Sharing the world without losing oneself: education in a pluralistic universe. Issue 5 (3rd September 2022) - O'Donnell, Aislinn
ABSTRACT: One of the challenges contemporary societies faces is resistance to sharing the world. Investments in 'extremist' or 'identitarian' identity positions that desire purity and are intolerant of pluralism and difference undermine education. I explain why it is important to explore 'how ideas feel', understanding the affective investments in these positions and imaginaries, and the fear of loss of identity that can drive such closed positions. In the second part, I turn to the writings of Édouard Glissant in order to deepen this analysis, paying particular attention to unpacking the desire for purity and the fear of métissage or mixing that are commonplace in racism, xenophobia, and ultra-nationalism. Glissant offers another way of understanding identity-in-relation whereby sharing the world does not mean losing oneself. Finally, I draw on his poetic language of archipelagic pedagogies to suggest some ways in which education can invite students to deepen a sense of world-oriented particularity.